2017
DOI: 10.1007/s10689-017-9966-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastric tumours in FAP

Abstract: Gastric cancer is not a recognised extra-colonic manifestation of FAP, except in countries with a high prevalence of gastric cancer. Data regarding gastric adenomas in FAP are sparse. The aim of this study was to review the clinical characteristics of gastric tumours occurring within an FAP population from the largest European polyposis registry. All patients that developed a gastric adenoma or carcinoma were identified from a prospectively maintained registry database. The primary outcome measure was the occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 28 publications
5
60
0
Order By: Relevance
“…Moreover, a recent work shows that even in advanced cancers, where other oncogenic mutations are detected, APC loss is crucial for tumor maintenance and its restoration may lead to tumor regression. 26 This is also consistent with other studies done in mouse models 27 and the human CRC cell line SW40, 28 demonstrating that restoring full-length APC alone attenuates tumor growth, despite other oncogenic mutations.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, a recent work shows that even in advanced cancers, where other oncogenic mutations are detected, APC loss is crucial for tumor maintenance and its restoration may lead to tumor regression. 26 This is also consistent with other studies done in mouse models 27 and the human CRC cell line SW40, 28 demonstrating that restoring full-length APC alone attenuates tumor growth, despite other oncogenic mutations.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous reports, in the present study, GN showed whitish coalescent nodules in the proximal stomach. 7,17 For early detection of GN in the AG-negative group, the above-mentioned characteristic findings are very useful.…”
Section: Discussionmentioning
confidence: 99%
“…In studies from Western countries, most cases were associated with FGP, and nearly half of these cases were of advanced cancer and showed a poor prognosis. 7,8,17 Regarding the association between gastric phenotype and GN with FGP, GN with advanced cancer seemed to have the gastric phenotype. In sporadic cases, the gastric phenotype had a high potential for malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upper gastrointestinal (UGI) tract surveillance has been recommended, starting from 25 years of age and has been shown to be beneficial. 3 Although the data are less, gastric adenomas and cancer are being noticed as newly emerging clinical problems [4][5][6] ; this may be partly due to increased endoscopic detection. More than 90% of patients will develop duodenal adenomas during their lifetime.…”
Section: Colorectalmentioning
confidence: 99%